2010
DOI: 10.1161/circulationaha.109.872481
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-1 Gene Therapy Enhances Angiogenic Signaling and Reduces Ventricular Remodeling in Infarcted Myocardium of Diabetic Rats

Abstract: Background-The present study evaluated the reversal of diabetes-mediated impairment of angiogenesis in a myocardial infarction model of type 1 diabetic rats by intramyocardial administration of an adenoviral vector encoding thioredoxin-1 (Ad.Trx1). Various studies have linked diabetes-mediated impairment of angiogenesis to dysfunctional antioxidant systems in which thioredoxin-1 plays a central role. Methods and Results-Ad.Trx1 was administered intramyocardially in nondiabetic and diabetic rats immediately aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 37 publications
4
85
0
1
Order By: Relevance
“…Thus, resveratrol increased longevity through its effects on SIRT1 and AKT in an in vivo myocardial stress model, suggesting the common activation mechanisms for AKT and SIRT1. 39 However, prior to our study, there were no data documenting the specific interplay between SIRT2 and AKT. We found that inhibition of NAMPT or SIRT2 induces strong acetylation of AKT, which is a new and exciting finding.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, resveratrol increased longevity through its effects on SIRT1 and AKT in an in vivo myocardial stress model, suggesting the common activation mechanisms for AKT and SIRT1. 39 However, prior to our study, there were no data documenting the specific interplay between SIRT2 and AKT. We found that inhibition of NAMPT or SIRT2 induces strong acetylation of AKT, which is a new and exciting finding.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, Nrf2 blockade was reported to suppress angiogenesis in mouse models in vivo (47). Moreover, the Nrf2 targets, heme oxygenase-1 (26, 34) and thioredoxin (67), were shown to confer pro-angiogenic effects in animal disease models, and Nrf2 activation was shown to confer significant anti-apoptotic effects in endothelial cells (75,76,77,78,91). Furthermore, treatment with a pharmacological activator of Nrf2 (resveratrol) was shown to both increase capillary density (60) and improve neurovascular coupling (73) in the aged brain, which were associated with improved cognitive function (60).…”
Section: Discussionmentioning
confidence: 99%
“…(40) XO is an oxidase that produces reactive oxygen species while SOD, an endogenous scavenger of superoxide, is responsible for destroying free superoxide radicals in the body. In the present study, incubation with 5 g/L Xiaokening for 72 hours reversed XO and SOD expression and activity in the arterioles of STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 99%